2022
DOI: 10.3390/en15114078
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Selected Torque Harmonics in a Three-Level NPC Inverter-Fed Induction Motor Drive

Abstract: The reduction or elimination of selected torque and current harmonics is widely used in multilevel inverter fed induction motor drives. A wide range of methods are employed to achieve this goal. Those modes of operation allow the avoidance of certain torque and current harmonics that may lead to disturbance and even mechanical and electrical resonance. In this paper, the selective harmonic elimination technique (SHE-PWM) is employed to reduce the chosen torque harmonics in a three-level NPC inverter-fed induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The papers presented in this Special Issue cover a wide range of selected problems of advances in electric traction systems [1][2][3][4][5][6][7][8], electric drives for ground and air transport [9][10][11], DC [12,13] and AC [14,15] power supply used in network traction, automation and control [16,17], and energy savings that help the environment [18].…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The papers presented in this Special Issue cover a wide range of selected problems of advances in electric traction systems [1][2][3][4][5][6][7][8], electric drives for ground and air transport [9][10][11], DC [12,13] and AC [14,15] power supply used in network traction, automation and control [16,17], and energy savings that help the environment [18].…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
“…Paper [11] addresses important issues involved in the initial application of AC motor drives supplied by inverters, i.e., the problem of the reduction in torque harmonics caused by distorted voltage delivered by inverter to a machine's terminals. Extensive literature in this area and applications of different methods of inverter control in multilevel inverters are presented.…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
“…Multi-level inverters have good application prospects in medium-voltage high-power motor drive systems [119], and they also have the switching freedom of the ZCM. A ZCM PWM scheme for a neutral-point-clamped (NPC) three-level inverter was proposed in [115].…”
Section: Advanced Topology For Zcm Modulationmentioning
confidence: 99%
“…Table 2, Refs. [30][31][32], present a comparative study of several three-level inverters, including PN-NPC (positive-negative NPC), T-type MLI, and 3L-ANPC ZCT (zero current transition), based on the number of components (including switches, diodes, inductors, and capacitors). The DC link, which consists of two capacitors (C 1 = C 2 ), is used to couple the FT 2 LI with the input dc supply.…”
Section: Development Of the Svpwm Algorithmmentioning
confidence: 99%
“…The research paper [30] proposes a hysteresis SVPWM reconfigurable fault-tolerant control technique for single-phase voltage source multilevel inverters with current tracking. The idea of employing the selective torque component elimination method is presented in article [31] in order to minimize a specific frequency of mechanical pulsations while achieving a full range of speed control. Paper [32] aims to investigate the electrical losses noted in a five-phase synchronous reluctance motor drive system and also attempts to study the electrical losses observed in this motor.…”
Section: Introductionmentioning
confidence: 99%